2012
DOI: 10.1158/1078-0432.ccr-11-3284
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial and Pharmacokinetic Study of Sorafenib in Children with Refractory Solid Tumors or Leukemias: A Children's Oncology Group Phase I Consortium Report

Abstract: Purpose To determine the dose-limiting toxicities (DLT), maximum tolerated dose (MTD), pharmacokinetics, and pharmacodynamics of sorafenib in children with refractory extracranial solid tumors and evaluate the tolerability of the solid tumor MTD in children with refractory leukemias. Experimental Design Sorafenib was administered orally every 12 hours for consecutive 28-day cycles. Pharmacokinetics (day 1 and steady-state) and pharmacodynamics were conducted during cycle 1. Results Of 65 patients enrolled,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
105
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 34 publications
11
105
0
2
Order By: Relevance
“…The mean C max observed in the NHP in this study was 5.8±2.1 μg/mL, while the day 1 C max in adult phase I studies of oral sorafenib for refractory solid tumors ranged from 2.3 to 3.0 μg/mL at the recommended dose of 400 mg twice daily [20]. At the MTD of 200 mg/m 2 /dose in a phase I trial of refractory solid tumors in children, the mean single day plasma AUC 0-24h was 28±17 μg•h/mL [21], which is similar to the mean plasma AUC 0-24h of 28±4.3 μg•h/mL in the NHP. Thus, the dose used in the NHP achieved sorafenib concentrations and exposure similar to those observed in both adults and children with refractory cancers at their respective recommended doses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean C max observed in the NHP in this study was 5.8±2.1 μg/mL, while the day 1 C max in adult phase I studies of oral sorafenib for refractory solid tumors ranged from 2.3 to 3.0 μg/mL at the recommended dose of 400 mg twice daily [20]. At the MTD of 200 mg/m 2 /dose in a phase I trial of refractory solid tumors in children, the mean single day plasma AUC 0-24h was 28±17 μg•h/mL [21], which is similar to the mean plasma AUC 0-24h of 28±4.3 μg•h/mL in the NHP. Thus, the dose used in the NHP achieved sorafenib concentrations and exposure similar to those observed in both adults and children with refractory cancers at their respective recommended doses.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma concentrations of sorafenib after oral administration in adult and pediatric phase I trials were highly variable across patients [21][22][23][24][25]. Some of the variability after oral dosing could be due to factors relating to absorption such as the potential slow dissolution of the tablets in the gastrointestinal tract [22].…”
Section: Discussionmentioning
confidence: 99%
“…A phase 1 study of sorafenib in children with refractory solid tumors and leukemia (ADVL0413) conducted by the Children’s Oncology Group (COG) Phase 1 and Pilot Consortium recommended a phase 2 dose of 200 mg/m 2 /dose every 12 hours continuously for children and adolescents with solid tumors and 150 mg/m 2 /dose for children with leukemia [4]. Similar to adults, common toxicities observed were rash, palmar-plantar erythrodysesthesia, hypertension, elevated serum transaminases, lipase elevation, diarrhea, and mild myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that sorafenib inhibits growth of human neuroblastoma tumor xenografts in mice by targeting both neuroblastoma cells and tumor blood vessels 6, 7. Sorafenib has been evaluated in pediatric patients with solid tumors or leukemia in two phase I studies in combination with other agents 8, 9 and, thereafter, in a Children's Oncology Group phase I trial as single‐agent therapy 10. Hypertension, diarrhea, rash, fatigue, and increased serum levels of alanine aminotransferase (ALT)/aspartate aminotransferase (AST) were the most common sorafenib‐related toxicities.…”
Section: Introductionmentioning
confidence: 99%